PENINGKATAN HASIL BELAJAR SOAL CERITA OPERASI HITUNG CAMPURAN DENGAN STRATEGI POLYA DI SD - Susianti, Fika (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study was to describe the form of an implementation plan and a story about the improvement of learning outcomes using mixed arithmetic operations Polya strategy in the sixth grade elementary school 01 Rantau Stone Ambacang. This research is a class act consisting of two cycles. Meetings were held in four stages: planning, implementation, observation and reflection phases. The approach used in this study is qualitative and quantitative approaches. Subjects were teachers and public school fourth grade students 01 Rantau Stone Ambacang. The test results of students at the end of the first cycle of action shows the average value, student learning outcomes (cognitive,, affective, and psychomotor) was 68% and at the end of the second cycle study the average value increased to 78%. Kata kunci : soal cerita, operasi hitung campuran, strategi polya